Bounds on Co-Independent Liar's Domination in Graphs. (20th March 2021) - Prabha, K. Suriya; Amutha, S.; Anbazhagan, N.; Cangul, Ismail Naci
Abstract : A set S ⊆ V of a graph G = V, E is called a co-independent liar's dominating set of G if (i) for all v ∈ V, N G v ∩ S ≥ 2, (ii) for every pair u, v ∈ V of distinct vertices, N G u ∪ N G v ∩ S ≥ 3, and (iii) the induced subgraph of G on V − S has no edge. The minimum cardinality of vertices in such a set is called the co-independent liar's domination number of G, and it is denoted by γ coi L R G . In this paper, we introduce the concept of co-independent liar's domination number of the middle graph of some standard graphs such as path and cycle graphs, and we propose some bounds on this new parameter.